Experimentos mentais e suas potencialidades didáticas - Michellan Kiouranis, Neide Maria [UNESP]; Souza, Aguinaldo Robinson de [UNESP]; Santin Filho, Ourides (Soc Brasileira Fisica, 2010)
A review of some articles on thought experiments shows that the use of these tools as resources seems to be very useful in understanding some phenomena that are very difficult to be observed in a real laboratory. In this paper we present an analysis and discussion about the very characteristics of though experiments as a potential instrument for physics teaching.
Thought experiments and its potentialities as didactic tools
Keywords: thought experiments; physics teaching; didactic resources